Enhanced Mechanical Properties Via the Incorporation of Ti in Cu Alloys - Huihui Yu; Qiang Hu; Yapan Huang; Yanqi Zeng; Jingxuan Jia; Q. Hu; Rui Hong; Youliang Zhang (Archives of Metallurgy and Materials)
The influence of Ti addition on the microstructure, mechanical properties and electrical conductivity of Cu-14Fe alloy is studied. Great emphasis has been laid on the second phase, texture and mechanical properties. No new phase other than α-Fe phase could be found in Cu-14Fe-0.1Ti alloy using XRD and SEM. With 0.1Ti addition, the distribution of α-Fe phase strip is slightly heterogeneous. Cube, s and brass texture components are largely strengthened in Cu matrix with Ti addition, while copper and goss texture components are rare in Cu matrix of both alloys. In α-Fe phases, α fiber and goss texture components are highly strengthened with Ti addition. It is found that enhanced mechanical properties are achieved in Cu-14Fe-0.1Ti alloy. In detail, with Ti addition, the yield strength and ultimate tension strength increase from 538 and 561 MPa to 580 and 583 MPa, respectively, while maintaining a high value of elongation to failure (6.5%). A lower equivalent grain size and a higher KAM value mainly contributes to the higher yield strengthening effect in Cu-14Fe-0.1Ti alloy. The lower equivalent grain size is derived from the small size distribution range and the small size of Cu matrix in Cu-14Fe-0.1Ti alloy. The dissolution of Ti and formation of nano second phases also improve mechanical properties. However, texture hardly plays a role in the strengthening effect. 0.1Ti addition hardly reduces the electrical conductivity of Cu-14Fe alloy, maintaining a value of 33.43% IACS. The results in this work could provide guidance in texture evolution and property evaluation in Cu-Fe alloys.